Mitigating Reputational Risk Through Image Repair Strategies. (June 2019) - Nair, Ramesh; Sulaiman, Shairah Hana; Saad, Nor Azyyati Md; Suppiah, Puspalata; Lin, Maizura
This article examines rhetorical strategies as well as the linguistic construction of those strategies in press releases put out by Cadbury Malaysia in response to accusations that it has failed to comply with halal certification standards. Drawing on image repair theory and the concept of the ideological square, six press releases were analysed to identify the rhetorical strategies as well as semantic structures that were used to repair the organization's image and minimize reputational risk. The analysis reveals how the organization moved beyond denial to also employ the rhetorical strategies of attacking one's accuser and bolstering. Despite early media reports naming government agencies as the accusers, the press releases put out by Cadbury Malaysia determined the source of accusations as unnamed individuals within the agencies, thereby avoiding confrontations with the relevant authorities. The analysis shows how language is used in press releases to construct the positive self and negative other as Cadbury Malaysia promoted a discourse of renewal to reassert its position within a highly lucrative halal market. This article provides novel insights into understanding how language works within rhetorical strategies of image repair.